2011
DOI: 10.1098/rsbl.2011.0098
|View full text |Cite
|
Sign up to set email alerts
|

Too much of a good thing? Variety is confusing in mate choice

Abstract: Choice variety is supposed to increase the likelihood that a chooser's preferences are satisfied. To assess the effects of variety on real-world mate choice, we analysed human dating decisions across 84 speed-dating events (events in which people go on a series of sequential 'mini-dates'). Results showed that choosers made fewer proposals (positive dating decisions) at events in which the available dates showed greater variety across such attributes as age, height, occupation and education, and this effect was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Finally, women were less responsive overall than men, mirroring findings from previous research (e.g. Kurzban & Weeden 2005;Todd et al 2007;Lenton & Francesconi 2011), but there was no influence of a woman's own height on her responsiveness (in line with Kurzban & Weeden 2005). Female height did, however, influence their desirability: women of average height were most desired during speed dating.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Finally, women were less responsive overall than men, mirroring findings from previous research (e.g. Kurzban & Weeden 2005;Todd et al 2007;Lenton & Francesconi 2011), but there was no influence of a woman's own height on her responsiveness (in line with Kurzban & Weeden 2005). Female height did, however, influence their desirability: women of average height were most desired during speed dating.…”
Section: Discussionsupporting
confidence: 79%
“…During a speed-dating event, participants meet approximately 10e30 individuals in a series of 3e7 min 'dates' after which they discretely indicate whether they are interested in further contact ('Yes'/'No'). When a 'Yes' is reciprocated, they make a 'Match', and contact details are subsequently provided to enable participants to arrange a more traditional date if desired (Kurzban & Weeden 2005Lenton & Francesconi 2011). Although such 'matches' do not inevitably lead to the formation of an actual relationship, people who were matched with at least one person during speed dating had a 10.9% chance of engaging in sexual intercourse with a 'match' within 6 weeks of the event, while the chance of a more serious relationship after 1 year was 7.2% (Asendorpf et al 2011).…”
mentioning
confidence: 99%
“…Studies have suggested that humans find it harder to choose when simultaneously presented with a large number of options, leading to lower choice satisfaction and motivation to choose (known as the ‘choice overload’ or ‘overchoice’ effect: Schwartz, ; Hutchinson, ). This effect has been seen when choosing dating partners (Lenton, Fasolo & Todd, ; Lenton & Francesconi, ) and food options (Iyengar & Lepper, ), and is assumed to arise due to the cognitive difficulties associated with comparing many options at once, rather than interference (Hutchinson, ). However, a meta‐analysis of the consumer choice literature suggests that across studies the average effect size is close to zero (Scheibehenne, Greifeneder & Todd, ), and it is unclear whether such effects are relevant to animal decision‐making.…”
Section: Number Of Options During Choice Testsmentioning
confidence: 99%
“…Fourth, all else is not necessarily equal, however, as greater choice can reduce the ability of choosy individuals to identify preferred items, including mates (e.g. consumers/shoppers: Lenton & Francesconi, ; but see Scheibehenne et al ., ; mate‐searching animals: Hutchinson, ; Alem et al ., ). The density of one sex and the OSR are related, and they covary perfectly if the population density is constant.…”
Section: Introductionmentioning
confidence: 99%